The Transformation of Anthropogenic Spatial Structures from Hunter-Gatherer Societies until Present Time. A Geographical View of the Material Effects of Changing Human-Environment Relations in the Light of Current Environmental Issues Der Wandel anthropogen geprägter Raumstrukturen von den Jäger- und Sammlergesellschaften bis zur Gegenwart Ein geographischer Blick auf die materiellen Auswirkungen sich verändernder Mensch-Umwelt-Beziehungen vor dem Hintergrund der aktuellen Umweltprobleme - Bätzing, Werner (Mitteilungen Der Osterreichischen Geographischen Gesellschaft, 2023)
The spatial structures, created by humans are more than just built infrastructures, but rather material expressions of human relationship with the environment. This article presents the various spatial structures that have developed throughout human history with their respective environmental references. The spatial structures of today are an expression of our serious environment problems (treating nature as material, infinite growth of economy and needs), and a solution to these problems is only possible, if these spatial structures are also fundamentally changed. At the same time, it becomes clear that a geographically integrative spatial analysis is still very important today.
CRIS-Team Scopus Importer:2024-12-16